Clinical utility of the global anti-phospholipid syndrome score for risk stratification: a pooled analysis. (12th January 2018) - Sciascia, Savino; Radin, Massimo; Sanna, Giovanni; Cecchi, Irene; Roccatello, Dario; Bertolaccini, Maria Laura
Abstract: Objective: Recently, our group conceived a risk score for clinical manifestations of APS (the global APS score, or GAPSS) that takes into account the combination of independent cardiovascular risk factors and the aPL positivity profile. These include hyperlipidaemia, arterial hypertension, aCL, anti-β2 glycoprotein-I, aPS-PT and the LA. A complementary version, the adjusted GAPSS (aGAPSS), which excludes aPS-PT, was also designed. The aim of our study was to systematically review the literature to assess the clinical utility of the GAPSS and aGAPSS for risk stratification of any APS clinical manifestation. Methods: We pooled data from available cohort studies, including a total of 10 studies, comprising 2273 patients, in which the GAPSS has been applied. A search strategy was developed a priori to identify an available cohort that reported findings which investigated the clinical utility of GAPSS or aGAPSS. Results: Seven studies used the GAPSS in their cohort, whereas three studies used the aGAPSS. In brief, we found a statistically significant difference in the cumulative GAPSS and aGAPSS between patients that experienced an arterial and/or venous thrombotic event [cumulative mean GAPSS (s .d .) 10.6 (4.74) and aGAPSS 7.6 (3.95)], patients without any thrombotic manifestation [cumulative GAPSS 7.01 (5.46) and aGAPSS 4.9 (4.33)] and patients with pregnancy morbidity [cumulative GAPSS 8.79 (2.59) and aGAPSS 6.7 (2.8)]. The highest levels of GAPSS were found in patients that experienced arterial thrombosis [mean GAPSS 12.2 (5.2)] and patients that experienced any recurrences of clinical manifestations of APS [mean GAPSS 13.7 (3.1)]. Conclusion: GAPSS may represent a useful tool to assess the thrombosis or pregnancy loss risk in aPL-positive patients, switching from the concept of aPL as a sole diagnostic antibody to aPL as risk factors for clinical events.